PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR ENERGI DI INDONESIA - Langgeng Prayitno Utomo (ICMA Nasional, 2024)
This research was conducted to analyze the impact of disclosure on environmental, social and governance (ESG) performance on a company's financial performance. The company's financial performance in this study is assessed by Return On Assets. The business of energy sector companies in Indonesia in 2018-2022 which are listed on the Indonesia Stock Exchange are the population of this study. The sampling method used purposive sampling to obtain a total of 9 energy sector companies whose annual reports and sustainability reports are published on their respective company websites. The method of analysis for environmental, social and governance disclosures is measured based on the GRI standard. The research findings show that ESG performance has a positive effect on financial performance. In further analysis, environmental disclosure and social disclosure show a negative effect on the company's financial performance. Conversely, disclosure of governance has a positive effect on financial performance